A comparison of perinatal outcomes in singletons and multiples born after in vitro fertilization or intracytoplasmic sperm injection stratified for neonatal risk criteria. (March 2014) - van, Mirjam M.J.; Evers, Johannes L.H.; Dumoulin, John C.M.; van der, Mark A.H.B.M.; van, Catharina E.M.; Bonsel, Gouke J.; Dykgraaf, Ramon H.M.; van, Johannes B.; Koopman‐Esseboom, Corine; Nelen, Willianne L.D.M.; Steiner, Katerina; Tamminga, Pieter; et al.
Abstract Objective To compare perinatal singleton and multiple outcomes in a large Dutch in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) population and within risk subgroups. Newborns were assigned to a risk category based on gestational age, birthweight, Apgar score and congenital malformation. Design Register‐based retrospective cohort study. Setting Netherlands Perinatal Registry data. Sample A total of 3041 singletons and 1788 multiple children born from IVF/ICSI in 2003–2005. Methods Student's t‐test or Mann–Whitney U‐test was used to analyze continuous data, chi‐squared analyses were used for categorical data. Multivariate logistic and linear regression analysis was performed to analyze whether the risk stratification criteria were associated with neonatal hospital admission and length of stay. Main outcome measures Start of labor, mode of delivery, gestational age, birthweight, 5‐min Apgar score, congenital malformation, neonatal hospital admission, neonatal intensive care unit admission and mortality. Results IVF/ICSI‐conceived multiples had considerably poorer outcomes than singletons in terms of cesarean section rate, preterm birth, birthweight, being small‐for‐gestational‐age, Apgar score, neonatal hospital admission, neonatal intensive care unit admission and neonatal mortality. As opposed to the results found in the total study population and the low‐risk and moderate‐risk populations, high‐risk multiples showed better outcomes than high‐risk singletons regarding cesarean section rate, birthweight and Apgar score. All risk stratification variables were associated with being hospitalized after birth. Length of stay was associated with all risk stratification criteria except Apgar score. Conclusions Perinatal outcomes in IVF/ICSI‐conceived multiples are considerably poorer than in singletons. This finding mainly pertains to low‐risk children. High‐risk multiples had significantly better perinatal outcomes than high‐risk singletons.